Library Information Literacy Programmes and Library Use by the Polytechnic of Ibadan Students - OYEWO, Rasaq Oyekanmi (MiddleBelt Journal of Library and Information Science, 2020)
Information Literacy (IL), as a concept, has its roots in the materialization of the information society. The importance of library information literacy programmes and library use by polytechnic students cannot be overemphasized. Education is being threatened by the poor performance of students in both public and private examinations which is making it difficult for students to achieve their aim in tertiary institutions. Hence, this study focus on the information literacy programmes and library use among the Polytechnic of Ibadan students. Cross-sectional survey style was adopted for this study. The study population consisted of 4382 HND students, using a sampling fraction of 10% which is 438 of the population of each faculty in the South Campus of the Polytechnic Ibadan, namely; Engineering, Science, Environmental Studies, Financial Management Science and Business and Communication Science. Questionnaire was used as the instrument for data collection. The data were analyzed using descriptive statistics of frequency and percentages. Results show that information literacy programmes and library use among the students is somehow moderate as majority of the students claimed orientation programme was made available for them. Majority (78.5%) of the students attested that library conduct regular user education for them, (38.9%) also confirmed that use of library is being taught as a course in their school. It was however found that one-third (31.3%) of the students agreed that the Internet provides everything they would need the library for, which is considered as a factor that affects the usage of the library. The study therefore, concluded that library information literacy programmes and library usage affect the use of library by the students both positively and negatively. The positive aspect is that it promotes the use of library and improves their academic performance while the negative aspect was that the students prefer the use of Internet than visiting the library. Therefore, the library should then intensify its orientation programmes since the Internet does not offer everything.